A Test Design Of English Grammar For The First Year Students Of SMUN I Kebakkramat - Hariyani, Hariyani (2006)
Grammar is one of elements of English therefore grammar test is very important. This test measures the student's ability to recognize appropriate grammar and structure especially tenses. The best type of grammar test is multiple choice. The items of multiple choice can be varied such as a completion, sentence alternatives, sentence interpretation, scrambleed sentence, completion (supply type). Grammar test is very difficult for the students therefore the writer is interested to know the type of a good English grammar test for the first year students of senior high school. The objective of the study is to design a good test of English grammar for the first year students of SMUN 1 Kebakkramat and to describe the validity and reliability of the test. The data of this study are the test items of English grammar design by the writer herself in accordance with supplementary English for senior high school by CV. Pustaka Mulia and English exercise for senior high school. 1B for the first year. The test consists of 30 items in the form of multiple choice. In order to find out the validity of the test, the writer analyzes the data systematically. In analyzing the data the writer uses the statistical analysis that is correlation product moment. x Based on the data analysis there are six items that are invalid and twenty four items are valid. The item is considered valid because the rdata 0,409 is bigger than rtable for N = 45 with the signification standard of 5% which is 0,294. And the item is considered in valid because rof data is smaller than rof table. The characteristics of valid items usually they are clear, and contain needed information within the option. Whereas the characteristics of invalid items are usually they are not clear and the distracters have similar meaning. So, in designing the test, test writers have to be careful in order to avoid the invalid items as seen as the data analysis. They also need to conduct a try out test in order to see the validity of test.